Biological Monitoring of Iodine Content in Human Breast Milk over Six Months Postpartum: A Case Study - Nor Hidayah Mohd Taufek; Aina Zafirah Azhar; Awis Sukarni Mohmad Sabere; Joseph Bidai (IIUM Press, International Islamic University Malaysia, 2024)
Iodine deficiency was commonly reported in infants and partly attributable to low breast milk iodine content. The role of iodine is crucial in preventing brain damage and hypothyroidism in infants. It is important to monitor the concentration of iodine in breast milk of postpartum mothers. This study aimed to validate an analytical method to determine iodine concentration in human breast milk for biomonitoring purposes. Expressed breast milk samples were collected several times a day throughout six months postpartum from a healthy lactating mother. Samples were prepared with nitric acid digestion and analysed by inductively coupled plasma mass-spectrometry. Data analysis was conducted using Microsoft Excel 2016 for assessment of validation parameters and longitudinal concentration of iodine. The method validation parameters showed that linearity of calibration graph was 0.9987, limit of detection and limit of quantification were 0.218 µg/L and 0.661 µg/L, respectively. A recovery of 100.3% showed good accuracy, whereas inter-day and intra-day repeatability were 5.91% and 3.60%, respectively. The median iodine concentration was the highest in the first month (160.0 µg/L), then dropped to lower than recommended level (110 µg/L) from the second until six months postpartum (range: 31.9 - 98.7 µg/L). Fluctuation in median iodine concentration occurred over six months postpartum but circadian rhythm was observed to be consistent with "V" shaped curve pattern indicating higher concentration was exhibited in the morning and at night compared to evening. The analytical method was robust, accurate and reliable for measuring iodine concentration in human milk and applicable for biomonitoring. Deficiency in breast milk iodine content was observed in the second until six months postpartum. Iodine concentration in breast milk exhibited consistent circadian variation over six months postpartum.